Impact of mask wearing time on fluid consumption and physical activity during the COVID-19 pandemic - Mitchell E. Zaplatosch; Mitchell E. Zaplatosch; Cory L. Butts; Samantha E. Scarneo-Miller; William M. Adams; William M. Adams; William M. Adams; William M. Adams (Frontiers in Nutrition)
PurposeTo examine the associations between mask-wearing on fluid consumption and physical activity behaviors during the COVID-19 pandemic.Methods137 college students (female, 72.5%; age, 26 ± 9 y) completed a survey detailing their fluid intake, physical activity behaviors, and time spent wearing a mask throughout the day during the previous month in the Fall 2020 academic semester.ResultsIncreased daily mask wearing time was not associated with total fluid intake (p > 0.05). Participants had greater odds of being ‘somewhat active’ compared to ‘inactive’ with an increase in mask wearing time (OR = 1.23 [1.03, 1.47], p = 0.022).ConclusionWearing a mask during the COVID-19 pandemic did not influence fluid intake behaviors, however, it increased the likelihood of reported greater levels of physical activity. These factors may be related to an individual being more likely to globally adopt healthier behaviors, however, this needs further exploration.